DEVELOPMENT OF A RANGE MEASUREMENT MODULE ON AN ULTRASONIC SENSOR WITH A GSM MODULE - Sotnik, S. V. (Radio Electronics, Computer Science, Control, 2025)
Context. The development of a range measurement module based on an ultrasonic sensor with a Global System for Mobile Communications (GSM) module is extremely relevant in the field of telecommunications and radio electronics. In today’s world, an increasing number of devices are integrated into Internet of Things (IoT) systems, where long-distance data transmission is provided by telecommunication technologies. The use of the GSM module allows real-time transmission of information from the measuring device to remote servers or end users, which is critical for remote monitoring and control solutions. Ultrasonic sensors in combination with a GSM module can automate measurement processes in hard-to-reach or hazardous environments, which increases the efficiency and safety of systems. The use of radio electronic technologies for real-time transmission of measurement data can significantly expand the functionality of devices and facilitate their integration into existing telecommunications systems, particularly in the industrial, transportation, and infrastructure sectors.Thus, the development of this module with precise measurements contributes to the development of innovations in the field of telecommunications and radio electronics, providing fast and reliable data transmission, which is an important component of modern information systems. Objective. Development of a range measurement module based on an ultrasonic sensor with a GSM module and improving the accuracy of measurements by implementing the proposed mathematical model of ultrasonic sensor autocalibration. Method. To achieve this goal, an integrated range measurement module was developed, which combines the HC-SR04 ultrasonic sensor with a GSM module. The method of improving accuracy is based on the proposed mathematical model of ultrasonic sensor autocalibration. Results. The task was stated, and a range measurement module based on an ultrasonic sensor with an integrated GSM module was developed. In the course of the study, an electrical schematic diagram of the device was created using DipTrace software. An printed circuit board has been created. A mathematical model of autocalibration of an ultrasonic sensor to improve measurement accuracy has been proposed. A series of experimental studies were carried out to assess accuracy. The results of the experiments confirmed the effectiveness of the developed module for measuring distances. Conclusions. The developed range measurement module based on an ultrasonic sensor with a GSM module is an innovative solution that meets the modern requirements of telecommunication and radio engineering systems. The integration of accurate distance measurement based on the proposed mathematical model of autocalibration of an ultrasonic sensor with the possibility of remote data transmission opens up new prospects for remote monitoring and automation of processes. Experimental studies have confirmed the accuracy and reliability of the device, and comparative analysis with analogs has demonstrated its competitive advantages. The costeffectiveness and energy efficiency of the developed module make it attractive to a wide range of users, from individual developers to industrial enterprises. Further research can be aimed at improving data processing algorithms and expanding the functionality of the device, which will contribute to the development of innovative technologies in the field of radio electronics and telecommunications.